Acute exposure to diesel particulate matter promotes collective cell migration in thyroid cancer cells - Cheng, Sheena Yi-Hsin; Huang, Shih-Yuan; Cheng, Shih-Ping (Frontiers in Toxicology, 2023)
Several ecological studies suggest that ambient air pollution is associated with the occurrence of thyroid cancer. In this study, we used certified diesel particulate matter as a proxy for fine particulate matter. Human thyroid cancer cell lines 8505C and TPC-1 were incubated with different concentrations of NIST1650b for 5 days and subjected to functional assays. We found that NIST1650b treatment did not affect short-term cell growth but reduced colony formation at high concentrations. Notably, NIST1650b-treated cells showed altered morphology toward cluster coalescence following treatment. Wound healing assays revealed that leading-edge cells formed protruding tips while maintaining cell-cell adhesion, and a significantly higher ratio of wound closure following treatment at 10 μg/mL was seen in both cell lines. A weak stimulatory effect on transwell cell migration was observed in 8505C cells. Taken together, our results suggest that fine particulate matter induced a coherent phenotype accompanied by augmented collective cell migration in thyroid cancer cells.